Present and Future Trend in the Production and Energy Consumption of Desalinated Water in GCC Countries - Fath, Hassan El-Banna (2013)
Water is one of the pressing global challenges facing humanity. In the Gulf Cooperation Council (GCC) countries, it is considered as the most critical challenges and is expected to grow with time. GCC countries have chosen desalination as the strategic water resource option and is, therefore, the world largest desalinated water producing regions. The objective of this study is to explore the current desalination technologies and their respective energy demands in GCC countries with different alternatives to reduce energy consumption. The paper presents and analyzes the present and the future prospective of water production rates and trends as well as the corresponding energy consumptions. The recent and historical desalination operational data have been studied and analysed and the results were presented using forecasted published data, up to the year 2025. Areas of possible efficiency improvements and reduction in the specific power consumption of the main commercially used desalination technologies; thermal (Multi Stage Flash (MSF) and Multiple Effect Distillation (MED)) and membrane (Reverse Osmosis (RO)) including the rehabilitation of present operating plants are presented. In addition, alternative energy sources such as renewable and nuclear as well as new desalination technologies of potential commercialization are also highlighted.